2010
DOI: 10.1038/ni.1963
|View full text |Cite
|
Sign up to set email alerts
|

ZAPS is a potent stimulator of signaling mediated by the RNA helicase RIG-I during antiviral responses

Abstract: Japan. 8 These authors contributed equally to this work. Correspondence should be addressed to A.T. (takaoka@igm.hokudai.ac.jp). At least three DExD/H-box RNA helicases 4,5 , RIG-I, MDA5 and LGP2 are included in the RLR family. RIG-I is a key PRR for the detection of positive-and negative-stranded RNA viruses in the cytoplasm of cells 6,7 , and plays an important role in triggering responses against many viruses, such as orthomyxovirus (influenza A virus) and paramyxovirus (measles, mumps, and Sendai virus (Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
216
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(225 citation statements)
references
References 57 publications
(60 reference statements)
9
216
0
Order By: Relevance
“…The short form of ZAP (hZAP-v2) was recently reported to stimulate the RIG-I signaling pathway (36). To analyze whether ZAP inhibits HIV-1 infection through the RIG-I pathway, RIG-I was depleted by RNAi in 293TREx-hZAP-v2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The short form of ZAP (hZAP-v2) was recently reported to stimulate the RIG-I signaling pathway (36). To analyze whether ZAP inhibits HIV-1 infection through the RIG-I pathway, RIG-I was depleted by RNAi in 293TREx-hZAP-v2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ZAP positively regulated RIG-I signaling during RNA virus infection in a human cell line (28). Therefore, we examined the involvement of ZAP in the RIG-I-dependent type I IFN response in primary mouse cells.…”
Section: Zap Does Not Regulate the Rig-i-dependent Type I Ifn Responsmentioning
confidence: 99%
“…Human ZAPL exhibits stronger antiviral activity than hZAPS against MuLV expression and Semliki forest virus infection (35) whereas both isoforms prevent HIV-1 infection (27). The ZAP isoforms are relatively broadly expressed in human tissues (35), but the mRNA expression of hZAPS is markedly increased by IFNα treatment (36). hZAPS is also more active than hZAPL in enhancing RIG-Idependent signaling in response to 5′-triphosphate-modified RNA, suggesting that regulation of ZAP activity can enhance or even amplify IFN responses (36).…”
mentioning
confidence: 99%
“…The ZAP isoforms are relatively broadly expressed in human tissues (35), but the mRNA expression of hZAPS is markedly increased by IFNα treatment (36). hZAPS is also more active than hZAPL in enhancing RIG-Idependent signaling in response to 5′-triphosphate-modified RNA, suggesting that regulation of ZAP activity can enhance or even amplify IFN responses (36). In addition, ZAPS and ZAPL are both polyADP ribosylated and have been implicated in stabilization of mRNA during cellular stress (37).…”
mentioning
confidence: 99%